2012
DOI: 10.1073/pnas.1200192109
|View full text |Cite
|
Sign up to set email alerts
|

Changing resonator geometry to boost sound power decouples size and song frequency in a small insect

Abstract: Despite their small size, some insects, such as crickets, can produce high amplitude mating songs by rubbing their wings together. By exploiting structural resonance for sound radiation, crickets broadcast species-specific songs at a sharply tuned frequency. Such songs enhance the range of signal transmission, contain information about the signaler's quality, and allow mate choice. The production of pure tones requires elaborate structural mechanisms that control and sustain resonance at the species-specific f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 54 publications
0
30
0
Order By: Relevance
“…When they studied the effect of aspect ratio on the resonances of plates that resembled the shape and structure of the wings of O. henryi, they found that changing the aspect ratio beyond the range of natural wings of O. henryi changed the deflection modes from their more efficient states in the real wings. unlike Sismondo (1979), who concluded that different cells of the forewings became the dominant resonators at different temperatures, Mhatre et al (2012) showed that wing cells did not resonate independently from one another but formed a single wing-shaped plate with different modes of vibration at different temperatures.…”
Section: Mechanics Of Sound Production In Anaxiphamentioning
confidence: 89%
See 3 more Smart Citations
“…When they studied the effect of aspect ratio on the resonances of plates that resembled the shape and structure of the wings of O. henryi, they found that changing the aspect ratio beyond the range of natural wings of O. henryi changed the deflection modes from their more efficient states in the real wings. unlike Sismondo (1979), who concluded that different cells of the forewings became the dominant resonators at different temperatures, Mhatre et al (2012) showed that wing cells did not resonate independently from one another but formed a single wing-shaped plate with different modes of vibration at different temperatures.…”
Section: Mechanics Of Sound Production In Anaxiphamentioning
confidence: 89%
“…Synchronization of forewing oscillations and file tooth impacts.-How insects as small as crickets can produce sounds that are nearly pure in frequency has long been of interest and talented researchers have studied the problem using increasingly sophisticated physical and electronic methods (e.g., nocke 1971, Sismondo 1979, koch et al 1988, Bennet-Clark 1999, Bennet-Clark & Bailey 2002, Montealegre-Z et al 2009, Mhatre et al 2012, robillard et al 2013. Most of these authors relied on crickets that are easily reared or otherwise conveniently available for laboratory studies and few were concerned with the effects of temperatures on the frequencies produced.…”
Section: Mechanics Of Sound Production In Anaxiphamentioning
confidence: 99%
See 2 more Smart Citations
“…As male tree crickets produce calls from a dipole that is highly directional (Toms 1984;Forrest 1991 Male O. nigricornis call frequencies are temperature dependent varying by over 1 kHz with changes in temperature across a range of 15 o C (Sismondo 1979). This change is known to be generated by their elongate wing geometry and its physical properties (Mhatre et al 2012). However, whether corresponding changes in the mechanics and neurophysiology of the ear maintain signal-receiver matching has yet to be established in Oecanthus.…”
Section: Matching Sender and Receivermentioning
confidence: 99%